2022
DOI: 10.1101/2022.08.12.503735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial communities of premise plumbing systems in four European cities, and their association with culturable Legionella

Abstract: Legionella species are Gram negative, facultative, intracellular bacteria found in natural and engineered water systems. Understanding the bacterial interactions underlying the success of Legionella in aquatic environments could be beneficial for control. We aimed to profile, by 16S rRNA amplicon sequencing, the bacterial communities in premise plumbing systems of buildings in four European cities (Copenhagen, Warsaw, Rome, Athens), and identify positive and negative associations of specific community members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Published data also confirm that hot water systems are an important reservoir from the point of view of risks to human health in which Legionella can multiply, especially if the water temperature is too low (<50 o C), there is a lack of flow or stagnant water and biofilm is present [10,14,15,16,17,19,20]. The persistence of such conditions in domestic distribution water systems, especially in facilities identified as a priority (e.g., hospitals or hotels), can pose a major threat to the health of the people using such systems [16,21,22]. Other factors conducive to the occurrence and proliferation of Legionella are oversized water systems, corrosion of construction materials, changes in water pressure, inadequate concentration of disinfectants or lack thereof, the presence of blind ends or dead legs, and seasonality of facility operation [10,11,14,17,19,23].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Published data also confirm that hot water systems are an important reservoir from the point of view of risks to human health in which Legionella can multiply, especially if the water temperature is too low (<50 o C), there is a lack of flow or stagnant water and biofilm is present [10,14,15,16,17,19,20]. The persistence of such conditions in domestic distribution water systems, especially in facilities identified as a priority (e.g., hospitals or hotels), can pose a major threat to the health of the people using such systems [16,21,22]. Other factors conducive to the occurrence and proliferation of Legionella are oversized water systems, corrosion of construction materials, changes in water pressure, inadequate concentration of disinfectants or lack thereof, the presence of blind ends or dead legs, and seasonality of facility operation [10,11,14,17,19,23].…”
Section: Introductionmentioning
confidence: 85%
“…In this case, infections are often associated by using showers when, through inhalation of contaminated aerosolized water, pathogens can enter the alveoli directly and result in infection [10,11,14,15,17]. Published data also confirm that hot water systems are an important reservoir from the point of view of risks to human health in which Legionella can multiply, especially if the water temperature is too low (<50 o C), there is a lack of flow or stagnant water and biofilm is present [10,14,15,16,17,19,20]. The persistence of such conditions in domestic distribution water systems, especially in facilities identified as a priority (e.g., hospitals or hotels), can pose a major threat to the health of the people using such systems [16,21,22].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the context of the microbial ecology of Legionella, the relevance of this is mainly linked to the observational studies aiming at understanding how this opportunistic pathogen lives in aquatic systems through their relationship with the surrounding organisms (Paranjape et al ., 2020, Paranjape et al ., 2020, Scaturro et al ., 2022). In a previous paper from our group, for example, we observed that Legionella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Paranjape and colleagues conducted two studies on cooling tower water and found that the genus Pseudomonas exhibited a strong negative correlation with Legionella, which, in turn, positively correlated with the genus Brevundimonas; the latter positive interaction has been further demonstrated in laboratory experiments with pure culture isolates. Scaturro and co-workers (Scaturro et al, 2022) investigated building plumbing water samples from several European cities and found positive correlations with bacteria of the genus Nitrospira, while observing negative associations with the genera Pseudomonas and Sphingopyxis.…”
Section: Introductionmentioning
confidence: 99%